In The Context of Fan Culture and Virtual Influencer Concepts The First Digital Fan: Leothefan - Serkan Karatay (Yeni Medya, 2024)
Social media platforms, which have become carriers of new communication and expression forms in digital environments, influence communication in personal, cultural, and societal contexts. These platforms, where expression and representation can be amalgamated through various modes of sharing, significantly enhance the visibility of influencers and fans. Additionally, social media has opened the door to the representation of techno-identities, where artificial intelligence-generated virtual characters can create their spheres of influence, manifest within the 'digital reality,' and reflect human passions. Leo constitutes the foundation of this study both as a fan/supporter and as a virtual influencer. The study, which is framed by the convergence of sports fandom and supporter practices with fan and influencer practices, also examines the relationship between media fandom and sports fandom. Concrete findings related to the topics addressed within the theoretical framework were sought through data obtained from the social media accounts of ‘Leo the fan’. The findings of the study reveal the relationship between sports fandom and media fandom with fan practices and influencer practices.